Evaluasi Fun Learning Pembelajaran SKI pada Generasi Alpha di MI Al Fitroh - Nafisah Izzah; Mohammad Sahlan; Sofyan Hadi (Edu Berkah Khatulistiwa, 2023)
Generation Alpha is a generation that is currently still classified as children, the highest age in the Alpha generation is still in elementary school. The Alpha generation also experienced when the world was hit by the Covid-19 wave when PSBB and PPKM were imposed by the government, making the Alpha generation stay in their respective homes, including learning online. Covid contributed to the Alpha generation to be more familiar with the digital world, the effect is that due to the lack of interaction with many people / the general public, many are very dependent on devices. The purpose of this study is to find an overview of the implementation of learning, efforts to provide fun learning methods and their evaluation by teachers in learning SKI in the Alpha Generation at MI Al Fitroh. Islamic cultural history stands alone as a subject that is part of Islamic religious education. The explanation obtained when the SKI lesson took place, many students were sleepy, bored or unfocused because the content of the material and the way the teacher delivered it were considered less than optimal. The research method used is descriptive qualitative, the final analysis uses SWOT. The findings in the field found that learning with the fun learning method was able to make Alpha generation students excited and enthusiastic in participating in SKI learning, but the evaluation stages carried out were too focused on the cognitive domain. Some things that must be considered in the future are field study learning, linking ibrah with evaluations that reach also emphasize the psychomotor and affective sides.